The Effect of Pozzolanic Material on Physical and Mechanical Properties of Construction Material - Saleemullah; Yasir Ansari; Kamran Ali; Muhammad Naveed Khalil; Ramez Raja; Muhammad Usman (Dialogue Social Science Review (DSSR), 2025)
The incorporation of additives like cement, fly ash, and marble dust into compressed earth blocks induces physical and mechanical alterations. Soil is randomly selected and sieved to remove larger particles. The specimens were produced in a 10 MPa hydraulic press. Pellets, or compressed earth bricks, were produced in this manner. A humidified compartment contained pellets for 28 days. Laboratory examination was conducted on all samples following a 28-day period. Three pallets exhibited diverse additive ratios. Pallets undergo a 28-day curing period prior to XRD, SEM, and EDX testing and processing. These additives enhance the mechanical properties of the material and contribute to advancements in the construction industry. The analysed sample contains a significant proportion of crystalline silica (Calcite). Alumina and haematite are also found in minor quantities in the samples. Alumina plays a crucial role in soil due to its ability to stabilise crude material composition and facilitate the dispersion of contaminants. Though their contribution is just a few percent, haematite particles may play a major role in the whole surface area of soils. Fly ash presence in samples exposes a significant number of pores with less than one millimetre in size. The bulk of crystalline structures are cubic and hexagonal ones. Among all these samples, silicon dioxide and calcium carbonate are more abundantly found. Local bricks have increased porosity and diminished mechanical strength due to ineffective and irrational neighbourhood heating and preparation techniques. The incorporation of slurry increases porosity. Due to their porosity, local bricks exhibit diminished mechanical strength. Cost reduction in post-block work was also attained. The layers of each block are now aligned. Owing to their diminished surface